Key role of AMPK in glucose-evoked Na,K-ATPase modulation - Rodrigues Costa, Ana (2012)
Background and aims: Na,K-ATPase is an integral membrane protein responsible for generating and maintaining transmembrane ionic gradients. It has been demonstrated that, in pancreatic β-cells, Na,K-ATPase is regulated by glucose and that this phenomenon is impaired in glucose intolerant subjects. However, the mechanism underlying glucose-induced modulation of Na,K-ATPase is still unclear. The AMP-activated protein kinase (AMPK) plays a key role in energy homeostasis, providing exquisite sensitivity to small changes in intracellular AMP. Since glucose has marked effects on oxidative metabolism and intracellular ATP and AMP levels in pancreatic β-cell, the involvement of AMPK in the cascade of events regulating Na,K-ATPase was postulated. The aim of this work was to evaluate the putative role of AMPK in the glucose-evoked regulation of Na,K-ATPase activity in the pancreatic β-cell. Materials and methods: Pancreatic -cells from normal (control) or glucose-intolerant Wistar rats (GIR) were isolated and cultured (48h). After a pre-incubation (30min) with 2.1mM glucose (G2), cell batches were challenged with G2 or G8 (8.4mM glucose) for 20min, in the presence or absence of AMPK agonist (AICAR 1mM) and antagonist (compound C (CC), 10μM). Na,K-ATPase activity was assessed in intact cells by quantification of Pi, in the absence and in presence of 1mM ouabain. Immunocytochemistry (ICC) of β-cells treated as previously described was performed using anti-α1-Na,K-ATPase and anti-phospho(ser-23)-α1-Na,K-ATPase antibodies. Western blots (WB) were performed in lysates of islets incubated in similar conditions plus AICAR or CC to evaluate α1-Na,K-ATPase (ser-23) phosphorylation. Results: In G2 the activity of Na,K-ATPase from normal and GIR pancreatic β-cell was similar (0.184±0.030 and 0.186±0.020 molPi/min/mgProt, respectively). Challenging the GIR β-cells with G8 evoked a significantly lower inhibition (40%) of Na,K-ATPase activity compared to a 62% inhibition observed in control β-cells. In control β-cell, the addition of AICAR abolished glucose-induced Na,K-ATPase inhibition (0,166±0.011 molPi/min/mg) whereas CC had no effect on glucose-induced inhibition of Na,K-ATPase. In the contrary, in GIR β-cells CC significantly potentiated glucose-evoked inhibition of Na,K-ATPase reaching values similar to that observed in the controls (66%). WB analysis revealed that Na,K-ATPase-α1 (ser-23) phosphorylation was increased by G8 (28±6% over basal) and abolished by AICAR. Additionally, CC induced an increase in phosphorylation equivalent to that observed in G8 (22±5% over basal). ICC showed an equivalent immunostaining intensity for α1-Na,K-ATPase despite glucose concentration. However, for the phosphorylated (ser-23) α1-Na,K-ATPase, a higher intensity was observed in cells exposed to G8 compared to G2. Conclusions: The AMPK agonist AICAR counteracts the inhibitory action of glucose on Na,K-ATPase of control β-cells whereas CC amplified the glucose-induced inhibition of Na,K-ATPase in GIR β-cells suggesting that AMPK plays a central role in the cascade of events underlying glucose-induced modulation of Na,K-ATPase and that the defect in GIR must be upstream of AMPK. The mechanism of glucose-induced inhibition of Na,K-ATPase may implicate AMPK inhibition by glucose metabolism and subsequent activation of PKC, that traditionally phosphorylates Na,K-ATPase in ser23. This mechanism must be uncoupled in GIR. Occurring prior to overt type 2 diabetes, this might be a feature in the disease development.